Efeitos do treinamento de força nas capacidades físicas de jogadores do basquetebol em cadeira de rodas - PINHEIRO , Joseana Araújo Bezerra Brasil (2019)
Introduction: The regular practice of wheelchair basketball by people with physical disabilities has high therapeutic value and benefits such as prevention of secondary disabilities, cardiovascular and musculoskeletal diseases, and contribute to improvements in factors such as body composition, lipid profiles and density. bone mineral. Wheelchair basketball is physically demanding and requires a high level of skill with complex techniques, tactics and physical qualities, requiring the wheelchair player to travel speed associated with rapid changes in direction and rapid upper limb strength. Objective: To analyze the effects of muscle strength training on different physical abilities in wheelchair basketball players. Methods: This is a quasi experimental study conducted from August 2018 to January 2019 at the Federal University of Maranhão with 8 wheelchair basketball players, 5 of them with spinal cord injury, 2 amputees, and 1 arthrogryposis victim. The players underwent anthropometric measurements of body mass, height, right and left arm circumference, waist, and then agility and speed tests. On the second day, they performed the handgrip strength tests and a maximum repetition. In agility, the adapted zigzag test was used; at speed the 40m running test on the sports wheelchair; For hand gripping, the portable dynamometer was used, obtaining an average of three attempts. The tests were performed at four times: initial, after 4 weeks, after 8 and after 12 weeks. After performing these tests, they underwent strength training for 12 weeks, performing the exercises: front pull, seated bench press, straight curl, French triceps, front and side elevations, wrist curl, inverted wrist curl. The loads were 60%, 70% and 80% of one repetition maximum, readjusted every four weeks. Shapiro-Wilk was used to verify data normality, one way analysis of variance with repeated measures and Tukey test. Results were demonstrated by mean and standard deviation, confidence interval, p value, delta percentage, effect size and statistical power> 80%. Results: The mean age of 36.5 ± 10.7; height 1.6 ± 0.1; body mass 67 ± 14.6; waist circumference 88 ± 11.6; from the right arm 32.6 ± 3.4; left 32.1 ± 2.6, Body Mass Index 25.1 ± 4.4. In agility, the 12-week period reduced the time traveled by 8.4%; at speed by 6.6%; In handgrip it was significant from the initial to 12 weeks in 10.4% right hands and 11.6% left hands. Conclusion: All players regardless of type of disability or functional classification had upper body muscle strength gains in 12 weeks of strength training, demonstrated by statistical significance, delta percentage, effect size and statistical power> 80%. Agility, speed and handgrip strength during the same training period were statistically significant, delta percentage gains, small and moderate or large effect sizes, but no statistical power> 80%.